Characterization of banana farms (Musa spp.) in Cuyani Microbasin, Pichanaki District, Chanchamayo Province (Junín, Perú) - Maraví, J. (2018)
The objective of this study was to characterize banana farms in the Cuyani Microbasin in the district of Pichanaki, Chanchamayo province (Junín, Peru). We worked with a producer organization that has 400 partners, of which a sample was taken (n = 80) using the proportions method. It was found that the banana farms are very diverse, the person in charge is mostly a man, but there is an interesting percentage of the female gender in the administration of the farms. In general, producers have a basic educational level. The production system is traditional, the banana is grown alone or associated with other crops, such as coffee. Most producers consider that pests and diseases are the main factors limiting production, since they reduce yields and increase production costs. The farms were classified in five groups, the most important of which was 45% of the farms whose owner is a male, between 44 and 56 years old, with secondary education, who lives on the same farm. They do not have a property title, the house does not have basic services, and they have poultry and guinea pigs. They have 2 to 3 hectares of banana (cultivars: Island and Palillo, 600 to 1000 plants/ha). Its production costs are between 2000 and 3600 soles and a yield of 6.5 to 7.5 t/ha. The cultivar Isla is the most common but also the cultivars Palillo, Morado and Biscocho are planted.